2017
DOI: 10.1111/dme.13515
|View full text |Cite
|
Sign up to set email alerts
|

Could FreeStyle Libre sensor glucose data support decisions for safe driving?

Abstract: AimMany countries require individuals with diabetes to adhere to standards regarding blood glucose testing in order to be granted or retain a driving licence. Currently, interstitial glucose results may not be used. The aim of this study was to determine whether interstitial glucose measurements using flash glucose‐sensing technology can provide additional information to augment safe driving.MethodsSensor data from two European studies (NCT02232698 and NCT02082184) of the FreeStyle Libre Glucose Monitoring Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Data has shown that trend arrows allow us to predict with accuracy what will happen in the next four hours, which has the potential to support assessment of safe glucose levels associated with driving. 28 The first postprandial hours and after insulin administration seem to be the moment where there may be less precision. 29 The precision of the two different systems -Dexcom G5 and FreeStyle Libre -seem to be similar.…”
Section: Interpretation Of Trend Arrows and Therapeutic Adjustmentsmentioning
confidence: 99%
“…Data has shown that trend arrows allow us to predict with accuracy what will happen in the next four hours, which has the potential to support assessment of safe glucose levels associated with driving. 28 The first postprandial hours and after insulin administration seem to be the moment where there may be less precision. 29 The precision of the two different systems -Dexcom G5 and FreeStyle Libre -seem to be similar.…”
Section: Interpretation Of Trend Arrows and Therapeutic Adjustmentsmentioning
confidence: 99%
“…Flash CGM was utilised in a blinded manner to demonstrate how hypoglycaemia can develop in people after they had demonstrated a satisfactory capillary blood glucose (>5 mmol/L is the recommended minimum for safe driving) after selected time intervals (Table 2). 35 CGM systems measure interstitial glucose and measurements obtained by CGM are currently not accepted by the DVLA as evidence of safe driving practice. The regulation states that 'blood' glucose measurements should be undertaken and not the interstitial tissue glucose concentration that is provided by CGM or flash glucose monitoring.…”
Section: Blood Glucose Retest Interval Recommended By the Dvlamentioning
confidence: 99%
“…Two studies have shown how these might be useful to detect hypoglycaemia occurring while driving, particularly asymptomatic episodes. 35,36 Continuous and often automatic monitoring of glucose levels would provide information to drivers which would alert them to potentially dangerous downward trends. Perhaps with the technological advances that are progressing apace with CGM and flash glucose monitoring, glucose sensors could be integrated within the display panel of a vehicle to alert the driver to a progressive fall in glucose.…”
Section: Blood Glucose Retest Interval Recommended By the Dvlamentioning
confidence: 99%
“…Rayman et al . , however, suggest that the FreeStyle Libre could support safer diabetes self‐management during driving, not by replacing but by prompting more frequent capillary glucose testing. Larger studies of longer duration are now indicated in high‐risk populations to evaluate the safety of both real‐time and intermittent glucose monitoring during driving.…”
mentioning
confidence: 99%
“…At present in the UK, the Driver and Vehicle Licensing Agency requires people taking insulin to test their capillary glucose prior to driving and does not recognize interstitial glucose measurements. Rayman et al [9], however, suggest that the FreeStyle Libre could support safer diabetes selfmanagement during driving, not by replacing but by prompting more frequent capillary glucose testing. Larger studies of longer duration are now indicated in high-risk populations to evaluate the safety of both real-time and intermittent glucose monitoring during driving.…”
mentioning
confidence: 99%